2016
DOI: 10.1177/1359105316664131
|View full text |Cite
|
Sign up to set email alerts
|

Proposal of an integrative model of adjustment to chronic conditions: An understanding of the process of psychosocial adjustment to living with type 2 diabetes

Abstract: Psychosocial adjustment to living with a chronic condition was explored in this grounded theory study, focusing on type 2 diabetes. Despite a range of relevant theories, there is limited understanding of the process of adjustment. The study aimed to address this issue. That was achieved through collecting and analysing personal narratives using individual interviews and focus groups. This allowed for the development of a normative integrative model of adjustment to chronic conditions based on biopsychosocial p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 26 publications
1
22
1
Order By: Relevance
“…Trigger: Challenging Situations -revision; change to Challenges. Contrary to the original IMACC study (Hammond and Hirst-Winthrop, 2018), we found that not only specific situations would trigger the maintenance cycle. Participants reported that a major challenge was the unpredictable nature of epilepsy, so even when a situation did not present a direct challenge, just the thought of what might happen was perceived as an ongoing challenge.…”
Section: Maintenance Cyclecontrasting
confidence: 99%
See 2 more Smart Citations
“…Trigger: Challenging Situations -revision; change to Challenges. Contrary to the original IMACC study (Hammond and Hirst-Winthrop, 2018), we found that not only specific situations would trigger the maintenance cycle. Participants reported that a major challenge was the unpredictable nature of epilepsy, so even when a situation did not present a direct challenge, just the thought of what might happen was perceived as an ongoing challenge.…”
Section: Maintenance Cyclecontrasting
confidence: 99%
“…One participant was able to reach a level of acceptance early, as she saw the epilepsy as the lesser of two evils: Learning New. As in the original IMACC study (Hammond and Hirst-Winthrop, 2018), three distinct types of learning were found: (1) the need for information and understanding (Knowledge), (2) the need to apply this in practical ways (Skills) and (3) the need to sometimes change old attitudes that might get in the way of optimal adjustment (Attitudes).…”
Section: Ongoing Adjustment Cyclementioning
confidence: 91%
See 1 more Smart Citation
“…One approach is to accept the disease, and try to integrate the demands of the disease into everyday life, thus attempting to master the disease in as constructive a way as possible. This approach was conceptualized into an integrative model of adjustment, developed from a qualitative study of patients with type 2 diabetes (Hammond and Hirst-Winthrop, 2016). The proposed model was characterized by three levels, that is, pre-morbid personality, on-going adjustment cycle, and maintenance cycle, and emphasizes the importance of acceptance of the disease (Costa et al, 2016), learning new knowledge, support, and integration into daily life activities.…”
Section: Discussionmentioning
confidence: 99%
“…Psychosocial adjustment is recommended as an integrative model for adaptation to chronic conditions in diabetes, as in other chronic diseases. 17 In a study conducted on individuals with type 2 diabetes, a positive relationship was found between psychosocial adjustment and treatment adherence. 18 Although psychosocial adjustment is diffi cult to assess, every data in this area seems to be very important 13,17,19 .…”
Section: Introductionmentioning
confidence: 99%